Electrical conductance of hydrogen chloride in dimethylsulphoxide at 25°C - Bolzan, J. A. (1970)
The electrical conductance of hydrogen chloride solutions in DMSO at 25°C has been studied. The limiting molar conductance is 38·7 int mho cm2 int mho cm2/mol. Conductivity data were interpreted with the Fuoss' theory for associated 1-1 type electrolytes. The association constant related to pair formation is 115·7 l/mol. The mechanism of electricl conduction of HCl in DMSO at infinite dilution resembles that of other 1-1 type electrolytes in the same solvent, in which charges are transported by simple entities in a viscous continuum.